Analisis Penerapan Budaya Keselamatan Pasien Di Instalasi Gawat Darurat Murni Teguh Memorial Hospital - Simanjuntak, Bertua Mitra Debora; Banjarnahor, Seriga (Universitas Murni Teguh, 2025)
Patient safety in the Emergency Room (ER) is a top priority, given the fast-paced and high-risk environment. The role of nurses in the emergency installation is crucial in implementinga culture of patient safety. Nurses are responsible for ensuring that every action, from triageto emergency care, is carried out carefully and according to hospital protocol. The objectiveof this study is to analyze the implementation of patient safety culture in health services atER in Murni Teguh Memorial Hospital. This study is a quantitative study with a descriptiveapproach. The population of the study was 52 nurses and doctors in the ER Murni TeguhMemorial Hospital, and 34 samples were obtained (26 nurses and 8 doctors), sampling wasdone using proportionate stratified random sampling. The data used were primary data andsecondary data. Data analysis was carried out descriptively which is presented in frequencydistribution table. The result shows that most of the health workers in the ER Murni TeguhMemorial Hospital with a good culture category of 97.1% and 2.9% with a moderate culturecategory. Patient safety culture based on each variable that the most health workers aregood culture is in the dimension of hospital management support (100%), dimension ofteamwork between units (76.5%). It is concluded that the implementation of patient safetyculture in the ER Murni Teguh Memorial Hospital is good. It is expected that all healthworkers at Murni Teguh Memorial Hospital maintain, continue, and develop patient safetyprograms that have been running and maintain a culture of patient safety. Furtherresearchers need to conduct further research using other variables such as work motivation,leadership, and others.